COLORECTAL CANCER PRESENTING WITH ANAEMIA. (8th June 2013) - Storm, J; Rafferty, G
Abstract : Introduction: British Society of Gastroenterology guidelines state that iron deficiency anaemia should be investigated and confirmed by a low serum ferritin, red cell microcytosis or hypochromia. The main objective of the guidelines is to diagnose significant pathology including colorectal cancer (CRC). Aims/Background: We analysed the number of patients with confirmed colorectal cancer that presented with anaemia and specifically to confirm the number of CRC cases that present with evidence of non-iron deficient anaemia. Method: We reviewed the haematology and biochemistry blood results of all Northern Health and Social Care Trust (NHSCT) patients with confirmed colorectal cancer in 2010. Results were obtained for the 12 months prior to diagnosis. Local laboratory criteria was used to confirm the normal range for blood results including Haemoglobin (Hb), Mean Cell Volume (MCV), serum ferritin, serum iron and Mean Cell Haemoglobin Concentration (MCHC) Results: 221 patients were diagnosed with colorectal cancer in 2010. Mean age was 71 (range 22-92). 50% were male. 49% were anaemic (Hb <12 g/dl). 31% had microcytic anaemia (MCV <83) and 18% had normocytic anaemia. 11 patients (5%) had an iron deficient normocytic anaemia. 18 patients (8%) had a normocytic anaemia but no iron studies performed. 11 (5%) patients diagnosed with CRC had a normocytic anaemia with normal serum ferritin and MCHC. For these 11 patients 9 charts were located and 6 had lower GI symptoms requiring colonoscopy but 3 (1%) were investigated as had low serum iron (but normal MCV, normal MCHC, normal ferritin and no lower GI symptoms). Conclusion: These results confirm that a significant proportion of CRC patients present with normocytic anaemia (18%). From these figures it suggests that 1% of the total CRC cases had asymptomatic normocytic anaemia with normal MCV, MCHC and serum ferritin. This however does not include the 18 patients with normocytic anemia that had unknown iron status as iron studies not performed. Iron studies should always be performed in investigating patients with microcytic/normocytic anaemia.